The importance of multidisciplinary and family support in children with Type 1 Diabetes Mellitus: an integrative review (Research, Society and Development, 2023)
Introduction: Multiprofessional support for families that have a child with DM1 seems to be essential, since this chronic condition directly interferes with the family's daily life and requires treatment that requires constant monitoring throughout life. Objectives: To analyze the importance of multidisciplinary and, above all, family support in children with DM1. Methodology: This is an integrative literature review, prepared and conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. The chosen databases were SciELO, LILACS and PubMed and the following descriptors were defined: “diabetes mellitus tipo 1”, “crianças” and “equipe multiprofissional” and their variations and combinations in English. Results and discussion: After the search, 9 articles were selected. According to the results, the multidisciplinary team acts in 3 ways in the care of children and adolescents with DM1: building long-term relationships, integrating knowledge through multidisciplinary teamwork and ensuring adequate documentation. Different professional groups must work as a team in order to provide optimal conditions for high-quality care for these patients. As for family support, it is essential for greater patient autonomy during treatment. Conclusions: The good relationship between the patient's family and the strong performance of a multidisciplinary team present are factors that directly and positively impact the results of the child's exams and their well-being.